Address at the opening of the Twenty-second Session - Monsell, William (Statistical and Social Inquiry Society of Ireland, 1869)
It has been the custom at the commencement of our annual sessions to direct attention to laws passed during the year, likely to affect our social or industrial progress, and to consider the remaining impediments to that progress, and the best means of overcoming them. The first subject will occupy us but for a few moments. The Industrial Schools' Act, which has worked successfully in England for the last fourteen years, has been extended to Ireland by a bill introduced and passed by The O'Conor Don. The only other measure to which I need refer is one in itself of great importance, and still greater on account of the principle involved in it?the transfer of the telegraphs of the United Kingdom to the government. For the rest, the last year is peculiarly worthy of observation. It closed the last series of five years that have elapsed since 1853, when the first vigorous effort was made to throw off the prostration caused by the great famine.
Read Friday, 22nd January, 1869
Keywords: Ireland in 1868; Irish economic performance; Irish agriculture; Irish legislation; 314.15